Small States and COVID-19: Cambodia's approach - Datta-Ray, Deep K. (2024)
Cambodia’s humanitarian, citizen-centric policies were applied flexibly to manage the COVID-19 pandemic. They may not have always been on target, but Cambodia’s successful management and containment of the virus with its very limited resources belies accusations of government politicking.